DO THEY MEAN WHAT THEY ACT? SURVEILLANCE, THEATRICALITY, AND MIND-HEART AMONG NORTH KOREANS - Jung, Hyang Jin (Acta Koreana, 2013)
In this article, I am concerned with the dynamics of self among North Koreans, in conjunction with their predicament of being under constant surveillance. To the outside world, the public behavior of North Koreans counts as one of the most puzzling aspects of the reclusive state, while many observers of North Korea point to a “real face” or “pure heart” behind the theatrical “public face” among North Koreans. Based on ethnographic interviews with visitors to North Korea and North Korean refugees, I explore the interweaving relations between the opposing modes of North Koreans’ selfpresentation: a theatrical “public face” and a non-theatrical “pure heart.” I argue that however contrasting they seem, the two modes of self-presentation are in support of, rather than in opposition to, each other for the purposes of the state. Exploiting the cultural notions of public and private and mind-heart, the North Korean state strives to make the face and the heart one and the same in piousness and loyalty. Yet the dramaturgical outlook of North Koreans begs a serious question as to the success of ideological indoctrination when an effort is made to co-opt the mind-heart of a people in the service of state sanctity.